Grow Up Entrepreneurial Interest for Cadets in Politeknik Penerbangan Surabaya Using CTL with Demonstration Methods - Setiawan, Ariyono; Munoto, Munoto; Nurlaela, Luthfiyah (Technium Social Sciences Journal, 2021)
In the current COVID-19 pandemic outbreak, the Indonesian nation is faced with various problems from health problems to economic problems. In this economic problem, a lot of companies have to lay off their employees. Also, in 2020 or during the COVID-19 pandemic era, many college graduates must be faced with reduced job vacancies, as well as competition from employees who have been dismissed. Therefore, it needs a serious handler from the government to employ or create decent and productive jobs through entrepreneurship education. The entrepreneurial field has deep freedom working to create economic independence to create jobs for others. Based on the results and discussion of the research described above, it can be taken the conclusion is that applying the CTL approach with demonstration methods can help generate interest in entrepreneurship cadet at a significance level of 0.05.